PHYSICAL AND MECHANICAL PROPERTIES LIGHTWEIGHT CONCRETE AND THE USE STYROFOAM SILICA SAND - Kurdian Suprapto; Mudji Irmawan; Fauzi Rahman (Journal of Civil Engineering, 2011)
The research is motivated rationale for reuse styrofoam waste (wrappers monitor) that is widely available on the ground that this cannot be destroyed or recycled. Utilization of waste is intended to not pollute the environment and can even be commercially valuable. In addition, this study is an attempt to find alternative materials replacement bricks. One of them is by using a mixture of portland cement, silica sand and styrofoam for the manufacture of non-structural lightweight concrete. Silica sand crushed into powder 22.44% retained on sieve no. 325 and styrofoam used in the form of small granules which pass 9.5 mm sieve. This study begins with a test mortar with silica sand content of 0%, 30%, 40%, 50% by weight of cement + silica sand. Then one of the mortar mixture composition is taken to be combined with Styrofoam to test concrete with styrofoam levels of 3%, 3.5%, 4% by weight of cement + silica sand. From the results of testing mortars, the composition of the mixture is taken as 40% silica sand and cement 60%. In testing the concrete, the greater the level of styrofoam, the smaller the volume weight, compressive strength, tensile strength and flexural strength concrete. The composition of concrete mixtures with styrofoam levels 3.5% and 4% which can be categorized as non-structural lightweight concrete material to be used as wall panels / insulation.